Pemanfaatan Situs Sejarah Candi Jabung Sebagai Sumber Belajar Untuk Meningkatkan Berpikir Kritis Mahasiswa IPS - Siti Nurul Hidayah (Jurnal Tinta, 2019)
This study aims to obtain an overview of the utilization of the historical temple site of Jabung to improve the critical thinking of social science students at the Islamic Institute of Islamic Sciences Zainul Hasan Genggong Probolinggo. The research method used is mixed methods, in which the form of this study combines two approaches namely qualitative and quantitative, this study uses data collection techniques of observation, interviews and tests. The results of data analysis from this study indicate that T count is -9.439 and T table is 1.742 which means that T count is greater than T table (-9.439>1.742) which means that the utilization of the temple history site as a source of learning can improve the critical thinking of IPS students , the results of this study can also be seen from the results of the tests between pretest and posttest, the test results showed that the average score of pretest was 72.00%, while the average score in the post test was 87.05%. The results of the pretest towards posttets increased by 15.05%. Based on the results of the analysis of the data, it can be concluded that in this study the utilization of the historical sites of Candi Jabung as an effective learning resource can improve the critical thinking of social science students.